Análise e modelagem de fósforo em reservatórios localizados em regiões semiaridas - Toné, Arthur Jordan de Azevedo (2016)
Eutrophication is the process by which water bodies are enriched with nutrients, often having phosphorus as limiting nutrient, with subsequent deterioration of its water quality due to excessive growth of aquatic phototrophic organisms. The fact that total phosphorus concentration is an indicator of trophic state and how dense is the algal biomass in lakes and reservoirs made it object of several models developed in order to predict its concentration and the factors that influence it. The high evaporation rates and average annual temperature, in addition to high hydraulic retention times (TR) values and great variability of total phosphorus concentrations, in reservoirs of semiarid regions requires a calibrated model for such systems as they are essentially different from those in temperate and tropical regions. In this sense, data from 33 reservoirs of Brazilian semiarid region were collected and a simple mass balance model for completely mixed lakes and reservoirs were analyzed, with only the phosphorus decay coefficient requiring (k) calibration. From the data obtained, it was found that the average total phosphorus concentrations in the studied reservoirs exceed those concentrations in temperate and tropical lakes and reservoirs, among which the Scots, New Zealanders, Americans, Canadians and Brazilians (in other regions of the country). Besides, the phosphorus loading to the analyzed reservoirs are of the same order of magnitude of those in other regions of Brazil, although having hydraulic retention times generally higher than those of temperate and tropical reservoirs, including Brazilians. From calibration the new relationship k = 4/√TR was obtained for Brazilian semiarid region, the double of that proposed for tropical lakes and reservoirs and four times higher than that proposed for those in temperate region, for the same TR, and it is consistent with the effects of higher temperatures which results in lower water viscosities and higher phosphorus consumption rates. The calibrated model was well adjusted to the data values of 30 of the 33 reservoirs of Brazilian semiarid region, with a high correlation coefficient (0,88) and it was validated with data from 08 reservoirs of the South African semiarid. The assessment of future scenarios demonstrated the usefulness of the proposed model for simulating different impacts in the reservoirs due to variations in their volume, inflows, phosphorus loads and removal percentages of affluent load. In this way, the model can be successfully used in modeling semiarid reservoirs in general and as a tool for more efficient management of water resources in these regions.